On the taxonomy of Sibynophis grahami (Boulenger, 1904) with remarks on morphology, distribution, natural history, and conservation status (Squamata: Sibynophiidae: Sibynophis) - Nguyen, Tan Van; Vogel, Gernot (Zootaxa, 2025)
Based on preserved specimens, including examination of available type materials and a comprehensive literature review, we reassess the taxonomic status in the Sibynophis chinensis auctorum. Our morphological analysis, in conjunction with recent molecular evidence provided by Guo et al. (2023), supports the elevation of Sibynophis chinensis grahami previously considered a junior synonym or subspecies of Sibynophis chinensis to a full species level, Sibynophis grahami. We restrict the distribution of Sibynophis chinensis to Central and Southern China including Taiwan Island, South Korea, and Northern Vietnam. We suggest Sibynophis grahami is likely edemic to the Yunnan-Guizhou (or Yungui) Plateau and considered as Least Concern (LC) following the IUCN’s Red List categories.